A novel solid self-nanoemulsifying drug delivery system (S-SNEDDS) for improved stability and oral bioavailability of an oily drug, 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol - Kyeong Soo Kim; Eun Su Yang; Dong Shik Kim; Dong Wuk Kim; Hye Hyun Yoo; Chul Soon Yong; Yu Seok Youn; Kyung Taek Oh; Jun-Pil Jee; Jong Oh Kim; Sung Giu Jin; Han Gon Choi (Taylor & Francis Group, 2017)
To develop a novel solid self-nanoemulsifying drug delivery system (S-SNEDDS) for a water-insoluble oily drug, 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) with improved stability and oral bioavailability, numerous S-SNEDDS were prepared with surfactant, hydrophilic polymer, antioxidant, and calcium silicate (porous carrier) using the spray-drying method. Their physicochemical properties were evaluated using emulsion droplet size analysis, SEM and PXRD. Moreover, the solubility, dissolution, stability, and pharmacokinetics of the selected S-SNEDDS were assessed compared with the drug and a commercial soft capsule. Sodium lauryl sulfate (SLS) and hydroxypropyl methylcellulose (HPMC) with the highest drug solubility were selected as surfactant and hydrophilic polymer, respectively. Among the antioxidants tested, only butylated hydroxyanisole (BHA) could completely protect the drug from oxidative degradation. The S-SNEDDS composed of PLAG/SLS/HPMC/BHA/calcium silicate at a weight ratio of 1: 0.25: 0.1: 0.0002: 0.5 provided an emulsion droplet size of less than 300 nm. In this S-SNEDDS, the drug and other ingredients might exist in the pores of carrier and attach onto its surface. It considerably improved the drug stability (about 100 vs. 70%, 60 °C for 5 d) and dissolution (about 80 vs. 20% in 60 min) compared to the commercial soft capsule. Moreover, the S-SNEDDS gave higher AUC, Cmax, and Tmax values than the commercial soft capsule; in particular, the former improved the oral bioavailability of PLAG by about 3-fold. Our results suggested that this S-SNEDDS provided excellent stability and oral bioavailability of PLAG. Thus, this S-SNEDDS would be recommended as a powerful oral drug delivery system for an oily drug, PLAG.